2022
DOI: 10.1002/nop2.1324
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural adaptation and validity of the nurse professional competence scale Korean version for graduating nursing students: An explanatory factor analysis

Abstract: The innovation of science and technology in healthcare systems and the increased need for quality of life among patients and families demands a redesigned academic model to foster graduates with high levels of competence, knowledge and skills (Mohieldein, 2017). Bryar et al. (2011 and the World Health Organization (2001) identified a group of professional competencies for Registered Nurses (RNs) that were important for providing patients with high-quality, safe care. In particular, there is strong evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
(96 reference statements)
1
2
0
Order By: Relevance
“…The original scale version as well as the country-specifically adapted NPC Scale Short Form versions in Saudi-Arabia, [34] China [36] and Croatioa [35] comprise item-specific nursing competencies under a total of six factors. [33] However, Lee et al [38] and Prosen et al [37] demonstrated altered scale structures after testing for construct validity, which was also revealed in our principal axis factor analysis results.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The original scale version as well as the country-specifically adapted NPC Scale Short Form versions in Saudi-Arabia, [34] China [36] and Croatioa [35] comprise item-specific nursing competencies under a total of six factors. [33] However, Lee et al [38] and Prosen et al [37] demonstrated altered scale structures after testing for construct validity, which was also revealed in our principal axis factor analysis results.…”
Section: Discussionsupporting
confidence: 77%
“…One consequence of this development is a presumed heterogeneity in the prevalence of particular nursing competencies in current Austrian nursing practice. This specific education-related heterogeneity is also reflected in the sample of our study and therefore might explain the prevalent differences towards item-specific competence estimations between the evaluated study samples in other European [32,35,37] and Asian [34,36,38] countries and our study cohort and, eventually, the subsequent change of the instruemnts' factorial structure.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation